Outcomes of a Telephonic Postnatal Intervention for Mothers and Babies in Mopani District, Limpopo, South Africa - Mutyambizi, Chipo; Dunlop, Jackie; Ndou, Rendani; Struthers, Helen; McIntyre, James; Rees, Kate (Frontiers in Global Women's Health, 2022)
Background The postnatal period is a critical period for the health of both mother and infant. Studies show that postnatal care reduces neonatal mortality and other adverse mother and child health outcomes. While the World Health Organisation recommends four postnatal care contacts, South African guidelines only specify three, excluding a 7-14-day post-birth contact. This study aimed to assess whether a telephonic contact at 7-14 days following delivery had any effect on use of additional postnatal services. Methods A randomised controlled trial design was used to address the study objectives. Two groups of new mothers were randomly allocated to either receive the 7-14-day telephonic contact or not from a research nurse. Data for this study was collected at Maphutha L Malatjie Hospital (MLMH). Descriptive analysis was performed first, then a multivariable logistic regression analysis was conducted to assess the factors associated with access to other health care services. Results A total of 882 mothers were recruited, 854 (97%) were classified as high risk, 28 (3%) were classified as low risk. 417 (49%) of the high risk received the 7-14-day call (intervention group) whilst the remainder of 437 (51%) from the high risk plus all mothers classified as low risk (28) did not receive the call (control group). 686 (78%) of all mothers received the 3 month follow up call. The call showed that 17 mothers from the control group and 10 mothers from the intervention group accessed other healthcare services. We find that hypertension (3.28; 1.06 -10.10), mental health risk (2.82; 1.25 - 6.38), PV bleeding during pregnancy (18.33; 1.79 - 187.61), problem during labor (4.40; 1.280 - 15.13) were positively associated with access to other health services, with statistically significant associations (p-value < 0.05). We found statistically insignificant associations between receiving the 7-14-day call and accessing other health care services. Conclusion The 7-14-day call had no statistically significant impact on access to other health services, however, high levels of satisfaction with the call may point to an unmet need for care at this time. It is important to investigate other innovative solutions to postnatal care improvement in South Africa.